Physical manifestations of violence on children in the teeth, jaw, and facial areas in odontology forensic - Wulandari, Ajeng; Riyanti, Eriska; Oscandar, Fahmi (Universitas Padjadjaran, 2015)
Introduction: Child abuse often occurs among children and leaves a negative impact on the rest of their life. The purpose of this study was to determine the significance of the manifestation of violence on the teeth, jaw, and facial from the view of odontology forensic. Methods: This study was descriptive research. Forty subjects were involved, which were taken using the purposive sampling method. Data obtained in the form of questionnaires and presented in tabular form. Results: The result has shown that 20.32% of the subjects had oral injuries. 20.32% of the subjects had oral bleeding, followed by bleeding gums, tooth bleeding, tooth mobility, tooth fractures, swollen gum, and swollen lips—injuries to the facial area including laceration, incision and burns. The highest incidence was 70.59% of facial injuries involving the middle third of the face, followed by the upper third, and then lower third of the face. Conclusion: The most manifestation of violence among the child abuse case involved are observed in dental and facial areas.